Manager’s ability, wage minimum policy, and firm size on firm performance: An empirical analysis in the real estate and construction sector - Ha, Nguyen Ho Phi (Accounting, 2021)
The real estate and construction industry have significantly played a particularly important role in economic development in each economy. In the case of Vietnam, the real estate and construction industry have greatly contributed a large proportion to the gross domestic product (GDP) growth with a sustainable annual growth. The purpose of this study is to examine the impact of manager’s ability, wage minimum policy, and firm size on firm performance. Using 220 real estate and construction firms in the case of Vietnam, results depict that a greater ability of managers in the real estate and construction sector will significantly enhance the efficiency of businesses. In addition, a larger firm can reach a higher firm efficiency while the efficiency of the real estate and construction firms is not impacted by changes of wage minimum policy.